Unprecedented shifts in aerosol pollution sources in China under a decade of clean air actions - Wenzheng Fang; Nikolaos Evangeliou; Sabine Eckhardt; Hang Xiao; Haibo Li (Communications Earth & Environment)
Abstract China is a major hotspot of black carbon (BC) emissions, contributing to climate warming and risk to public health. Here, our dual-isotope-constrained observations indicate stringent air pollution controls have drastically reduced coal-burning in North China over the past decade, marking a transition to a “post-coal” era compared to earlier 2012–2014. However, biomass-burning fraction (f bb) for north/central/east winter hazes has doubled from earlier (north/east) ~20%, with significantly higher f bb during polluted winters. Comparisons between observation and transport modelling show good alignment in BC concentrations but substantial discrepancies in source attribution (i.e., f bb). Leveraging radiocarbon measurements, advanced atmospheric modelling, and a Bayesian approach, our study identifies biases stemming from misallocated residential fuel types in emission inventories. These findings underscore the untapped potential to mitigate BC emissions by targeting rural biomass burning, while providing critical insights into BC source evolution to refine emission inventories and formulate effective air quality policies for China and other nations facing severe air pollution.